The world in play : portraits of a Victorian concept - Kaiser, Matthew (Stanford University Press, 2012)
19th-century Britain was a world in play. The Victorians invented the weekend and built hundreds of parks and playgrounds. The playful child became a symbol for the future. This book explores the extent to which play pervades 19th-century literature and culture.